Digital communication in the mobilization and resistance of indigenous of Colombia - Salazar Torres, Neyder Jhoan (2017)
This text addresses the use of digital communication of the Colombian indigenous movement, from the cases of the Communication Fabric of the ACIN and the Collective Winds of the CRIHU, for this it focuses on the analysis of the actions of mobilization of the Minga Indígena and Popular of 2008 and the recovery of Cerro El Berlín, held in Cauca and the Mingas of Liberation of Mother Earth in 2012 and 2013, held in Huila. Fundamental mobilizations in the historical struggle and the indige nous resistance, in these they articulated communicative and digital strategies, the appropriation of diverse supports and technological repertoires to counter the stigmatization of the hegemonic means and the reproduction of the state voice, thus to potentiate the political communication since Action and resistance.